2011
DOI: 10.1124/jpet.111.183020
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drug Flufenamic Acid Is a Potent Activator of AMP-Activated Protein Kinase

Abstract: Flufenamic acid (FFA) is a nonsteroidal anti-inflammatory drug (NSAID). It has anti-inflammatory and antipyretic properties. In addition, it modulates multiple channel activities. The mechanisms underlying the pharmacological actions of FFA are presently unclear. Given that AMP-activated protein kinase (AMPK) has both anti-inflammatory and channel-regulating functions, we examined whether FFA induces AMPK activation. 1) Exposure of several different types of cells to FFA resulted in an elevation of AMPK␣ phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…In fact, AMPK has recently been shown to play many pivotal roles in regulating epithelial functions including facilitation of tight junction assembly and inhibition of CFTR-mediated chloride secretion [4,7]. In addition, several studies have shown that some known drugs such as aspirin and fenamates activate AMPK, which may account for the antiinflammatory and chemopreventive effects of these drugs [22,23]. In the present study, COS with the averaged MW of 5,000 Da had more pronounced AMPK-stimulating effect than those with higher MW (8,000 Da, 14,000 Da and 100,000 Da).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, AMPK has recently been shown to play many pivotal roles in regulating epithelial functions including facilitation of tight junction assembly and inhibition of CFTR-mediated chloride secretion [4,7]. In addition, several studies have shown that some known drugs such as aspirin and fenamates activate AMPK, which may account for the antiinflammatory and chemopreventive effects of these drugs [22,23]. In the present study, COS with the averaged MW of 5,000 Da had more pronounced AMPK-stimulating effect than those with higher MW (8,000 Da, 14,000 Da and 100,000 Da).…”
Section: Discussionmentioning
confidence: 98%
“…We therefore tested whether AMPK could attenuate the cytotoxic effects of ADR. For this purpose, we have used three structurally different AMPK activators, which are known to activate AMPK through different signaling mechanisms (Wang et al, 2003;Shaw et al, 2005;Chi et al, 2011). As shown in Fig.…”
Section: And E)mentioning
confidence: 99%
“…Cellular lysates were subjected to Western blot analysis for phosphorylated P38. these chemicals activate AMPK through different signaling mechanisms (Wang et al, 2003;Shaw et al, 2005;Chi et al, 2011), their effects must be due to activation of AMPK. In further support of this notion, suppression of AMPK with compound C exaggerated ADR-induced activation of ASK1/ P38 and loss of cellular viability.…”
Section: Ampk Attenuates Oxidative Cell Injurymentioning
confidence: 99%
“…In fact, AMPK activators have been shown to inhibit inflammation in various model systems (4,22,33,34). On the other hand, some of the well-known anti-inflammatory drugs have also been reported to activate AMPK (5,15).…”
mentioning
confidence: 99%